Students' science attitudes, beliefs, and context: associations with science and chemistry aspirations. Issue 6 (13th April 2018) - Mujtaba, Tamjid; Sheldrake, Richard; Reiss, Michael J.; Simon, Shirley
ABSTRACT: There is a widespread concern that relatively few students, especially those from disadvantaged backgrounds, continue to study chemistry and other science subjects after compulsory education. Yet it remains unclear how different aspects of students' background and home context, their own attitudes and beliefs, and their experiences of particular teaching approaches in school might limit or facilitate their studying aspirations; concurrently, less research has specifically focused on and surveyed disadvantaged students. In order to gain more insight, 4780 students were surveyed, covering those in Year 7 (age 11–12 years) and in Year 8 (age 12–13) from schools in England with high proportions of those from disadvantaged backgrounds. Predictive modelling highlighted that the students' aspirations to study non-compulsory science in the future, and to study the particular subject of chemistry, were strongly associated with their extrinsic motivation towards science (their perceived utility of science, considered as a means to gain particular careers or skills), their intrinsic interest in science, and their engagement in extra-curricular activities. Additionally, their self-concept beliefs (their confidence in their own abilities in science), some teaching approaches, and encouragement from teachers and family alongside family science capital had smaller but still relevant associations.